Metavert synergises with standard cytotoxics in human PDAC organoids and is associated with transcriptomic signatures of therapeutic response - An, Jingyu; Kurilov, Roman; Peccerella, Teresa; Bergmann, Frank; Edderkaoui, Mouad; Lim, Adrian; Zhou, Xu; Pfütze, Katrin; Schulz, Angela; Wolf, Stephan; Hu, Kai; Springfeld, Christoph; et al. (Translational oncology, 2024)
Background - Despite some recent advances, pancreatic ductal adenocarcinoma (PDAC) remains a growing oncological challenge. New drugs capable of targeting more than one oncogenic pathway may be one way to improve patient outcomes. This study characterizes the effectiveness of Metavert a first-in-class dual inhibitor of GSK3-β and histone deacetylase in treating PDAC as a single agent or in combination with standard cytotoxics. - Methods - Thirty-six Patient-Derived Organoids (hPDOs) characterised by RNASeq and whole exome sequencing were treated with Metavert alone or in combination with standard cytotoxics. Transcriptomic signatures (TS) representing sensitivity to Metavert alone or sensitivity to Metavert + irinotecan (IR) were evaluated in 47 patient samples, chemo-naïve in 26 and post-chemotherapy in 21 (gemcitabine=5; FOLFIRINOX=14, both=2) with companion multiplexed immunofluorescence and RNASeq data. - Results - Metavert combined with gemcitabine, irinotecan, 5FU, oxaliplatin, and paclitaxel was synergistic in the hPDOs. Basal-subtype hPDOs were more sensitive to Metavert alone whereas the Metavert+IR combination exhibited synergy in Classical-subtype hPDOs with increased apoptosis and autophagy. hPDO-derived TS evaluated in PDAC tissues demonstrated that Metavert-TSHi samples were enriched for mRNA splicing and DNA repair processes; they were associated with Basal-like tissues but also with GATA6+ve-chemo-naïve samples and were higher following gemcitabine but not FOLFIRINOX treatment. In contrast, Metavert+IR-TSHI samples were enriched for TP53 pathways; they were associated with Classical-like pretreatment samples and with GATA6+ve/KRT17+ve hybrid cell types following FOLFIRINOX, but not gemcitabine treatment, and were unrelated to transcriptional subtypes. - Conclusions - Metavert as a single agent and in combination with irinotecan offers novel strategies for treating pancreatic cancer.